(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Banks was one of the institutions that are highly concerned with the issue of performance evaluation, in order to achieve optimal use of resources that enable them to achieve operational and strategic objectives both in light of the global competition fierce for the start of the research problem of banks to adopt in assessing the performance of the realization of just the traditional financial indicators which has become insufficient to keep pace with the constant evolution in the business environment, which requires work on the use of the necessary information needed to evaluate the performance of all the Bank’s activities through the use of the Balanced Scorecard method. The research aims to shed light on the dimensions of performance metrics and Balanced Scorecard and the statement of the impact of the application of balanced performance to improve the performance of the Rafidain Bank card as well as a statement of the amount of satisfaction of employees and customers on the services provided by the bank.